Domestic Violence in COVID-19 Pandemic Era from January to September 2021 in Manado - Phoebe C. A. Pangalila; James F. Siwu; Nola T. S. Mallo (e-CliniC, 2022)
Abstract: Domestic violence has been reported globally in various countries, including Indonesia. The COVID-19 pandemic has intensified this issue, regardless the decrease shown in the number of cases reported. This study aimed to obtain the incidence rate of domestic violence, its influencing factors, and forms of domestic violence during the COVID-19 pandemic in Manado from January to September 2021. This was a retrospective and descriptive study with a cross-sectional design. Secondary data were domestic violence cases reported in Manado Women Empowerment and Child Protection Service. The results showed 11 reported cases. Mapanget and Wanea were districts that received the most reports. Victims were dominated by females who were wives, children, or niece of the perpetrators, aged under 18 years old, mostly under 5 years old. Household neglect was the most form of domestic violence. In conclusion, domestic violence cases reported in Manado from January to September 2021 were dominated by female victims and children of the perpetrators. The COVID-19 pandemic and patriarchal culture were suspected as indirect triggers in terms of household neglect as the most common form of domestic violence.Keywords: COVID-19 pandemics; domestic violence Abstrak: Kekerasan domestik (KDRT) telah dilaporkan secara global di beragam negara, termasuk Indonesia. Pandemi Covid-19 turut memperhebat kasus ini walaupun jumlah laporan kasus justru menurun. Penelitian ini bertujuan untuk memperoleh gambaran angka kejadian KDRT, faktor yang memengaruhinya, serta bentuk KDRT di Kota Manado pada saat pandemi Covid-19 periode Januari–September 2021. Jenis penelitian ialah deskriptif retrospektif dengan desain potong lintang menggunakan data sekunder, yakni laporan kasus KDRT yang dikumpulkan dari Dinas Pemberdayaan Perempuan dan Perlindungan Anak Kota Manado. Hasil penelitian mendapatkan 11 kasus terlapor, dengan Mapanget dan Wanea sebagai kecamatan yang menerima laporan terbanyak. Korban didominasi oleh perempuan yang merupakan istri, anak, serta keponakan pelaku yang berusia di bawah 18 tahun, terbanyak ialah anak berusia kurang dari 5 tahun. Bentuk kekerasan terbanyak dialami ialah penelantaran rumah tangga. Simpulan penelitian ini ialah kasus KDRT terlapor di Kota Manado pada Januari-September 2021 didominasi oleh korban berstatus anak pelaku berusia kurang dari 5 tahun dan berjenis kelamin perempuan. Pandemi Covid-19 dan budaya patriarki disinyalir menjadi pemicu tidak langsung dilihat dari penelantaran rumah tangga sebagai bentuk KDRT terbanyak.Kata kunci: pandemi Covid-19; kekerasan dalam rumah tangga